If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 3 = 2n + 4 Reorder the terms: 3 + 5n = 2n + 4 Reorder the terms: 3 + 5n = 4 + 2n Solving 3 + 5n = 4 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 3 + 5n + -2n = 4 + 2n + -2n Combine like terms: 5n + -2n = 3n 3 + 3n = 4 + 2n + -2n Combine like terms: 2n + -2n = 0 3 + 3n = 4 + 0 3 + 3n = 4 Add '-3' to each side of the equation. 3 + -3 + 3n = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 3n = 4 + -3 3n = 4 + -3 Combine like terms: 4 + -3 = 1 3n = 1 Divide each side by '3'. n = 0.3333333333 Simplifying n = 0.3333333333
| (x+2)*y=90 | | 5x=z-5h | | (x+2)*y=216 | | (x-2)(y+18)=216 | | z=5(x+h) | | 3c=7.35 | | a^2-12ax+32x^2=0 | | c^2-cy-12y^2=0 | | 2b-22/b-11 | | (xy^2+x)dx+(xy^2+y)dy=0 | | 1. 3a=4a+8 | | 3x+21=108 | | -(-5v+y)+6(2y-5v)= | | 3*-5y=15 | | 12x+18y=1 | | y=-x^2+4x+45 | | 3*0-5y=15 | | 2x-1/2x=0 | | 10=2(y-3)-6y | | 2.5x-7.5=x | | x-2*-2=6 | | -40+6p+p^2= | | 2xyz-10xy-49y= | | 3(x-2)+12=6x+5-3x | | 3x^2-22x-7=0 | | -75727.82/87.08= | | 39.76-(6.46)+(53.78)= | | 41.4-8.8(-75.2)(-114.5)+2.3= | | -1530-(-573)= | | 10+5x=5y | | 4-(-0.25)-0.5= | | c^2-17c+72= |